Suitability of Chicken EPGCS on Different Cryoprotective System - LI, B.C.; Chen, H.; Xiao, X.J.; Han, Wei; Xu, Qi; Xinsheng, Wu; Bao, Wenbin; Chen, G.H. (International Journal of Poultry Science, 2007)
The objective of this study was to evaluate the effect of three cryorotectants (at three concentration each) and two cryopreservation protocols on the preservation of chicken Primordial Germ Cells (PGCs) from gonads at stage 19 and stage 28. The PGCs were cryopreserved using Dimethylsulphoxide (DMSO; 10%, 20%, 30%), glycol (GLY; 10%, 20%, 30%), polyethylene glycol (PEG; 10%, 20%, 30%). In a first series of experiments, we compared viability after three cryorotectants based protocol I and found the viability of PGCs showed very significant percentage (86.53%) (p<0.01) in a freezing media IV. We then compared an cryopreserve protocol I with 5% dimethyl sulfoxide (DMSO)+5% Glycol versus a cryoprotectant protocol II and observed a better viability with the former protocol (85.9% versus 67.4%, p<0.05). Finally, we compared viability of PGCs at three concentration each cryorotectant and found no significant difference p>0.05 between the concentration of 10% and 15% except freezing media III. When the concentration was 20%, the viability of PGCs was the lowest and showed significant difference p<0.05 or very significant difference (p<0.01) compared to other concentration. In conclusion, 5% DMSO+5%GLY with cryopreserve protocol I was the most effective cryopreservation for chicken primordial germ cells.